Possible PHACES syndrome: segmental thoracobrachial hemangioma associated with extracutaneous manifestations. - Manunza, F.; Ferreli, C.; Cordisco, M.R.; Pau, M. (European Journal of Pediatric Dermatology, 2014)
In PHACES syndrome a facial infantile hemangiomas (IH) is associated with extracutaneous manifestations involving the central nervous system, heart, blood vessels of head and neck, eye and sternum. Recently, an IH of the upper trunk was reported in association with extravcutaneous manifestations reminiscent of PHACES syndrome. Here we report a case of a 7-month-old girl with segmental hemangioma involving the upper trunk and limb. It was associated with structural anomalies similar to those reported in PHACES syndrome, including congenital heart disease, arterial abnormalities and a sternal defect; moreover there was a late-onset small hemangioma of the face.